2014
DOI: 10.1051/limn/2014009
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and biotic variables as potential predictors ofLudwigia sedoides(Humb. & Bonpl.) Hara in a large Amazonian reservoir

Abstract: -Reservoirs cause hydrological changes (i.e., water level stabilization) that favor the colonization of aquatic macrophytes. Knowing the ecological factors that determine the occurrence of these plants is critical for water management (e.g., plant control) and biodiversity conservation. In this sense, the present study investigated colonization patterns of Ludwigia sedoides in Lajeado reservoir (Tocantins River, Amazon Basin), in order to identify variables that influence colonization at habitat scale. We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Our results confirm these biotic gradients in Lajeado Reservoir, but some species colonized the whole gradient, probably because the littoral zone in this reservoir favor the development of aquatic plants, i.e. extensive shore development, shallow depths (<2m), gentle slopes, stable water level, high water transparency and sites protected by wind/wave action (Lolis & Thomaz, 2011;Barbosa et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Our results confirm these biotic gradients in Lajeado Reservoir, but some species colonized the whole gradient, probably because the littoral zone in this reservoir favor the development of aquatic plants, i.e. extensive shore development, shallow depths (<2m), gentle slopes, stable water level, high water transparency and sites protected by wind/wave action (Lolis & Thomaz, 2011;Barbosa et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Slope is another important factor for emergent macrophytes, because it directly affects sediment grain size, chemical composition and stability; these conditions affect negatively plant anchoring and growth (Bornette & Puijalon, 2011). Barbosa et al (2014) observed that slope, together with fetch and depth, are the main factors regulating the coverage and distribution of L. sedoides in Lajeado Reservoir. The present study, however, included sites with gentle slopes, so this variable may have a secondary role influencing the distribution of emergent macrophytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations